Capacitive deionization concept based on suspension electrodes without ion exchange membranes - Hatzell, Kelsey B.; Iwama, Etsuro; Ferris, Anais; Daffos, Barbara; Urita, Koki; Tzedakis, Théodore; Chauvet, Fabien; Taberna, Pierre-Louis; Gogotsi, Yury; Simon, Patrice (Electrochemistry communications, 2014)
A new type of capacitive deionization (CDI) system, based on capacitive suspension electrodes (CSEs), was developed for the purpose of desalting brackish and seawater through the use of flowable carbon suspensions. CSEs derived from activated carbon and acetylene black demonstrated a specific capacitance of 92Fg−1 in a static mode in a 0.6M NaCl solution. The novel system introduced here is a proof of concept that capacitive suspension electrodes can be envisioned to desalt water without the aid of ion exchange membranes (IEMs). [Display omitted] •Capacitive deionization (CDI) with capacitive suspension electrodes is shown.•Potentiometric titrations of cathode suspension demonstrate chloride adsorption.•Spherical carbon particles demonstrate greater adsorption capacity in 0.6M NaCl.